Validation of the Hsp70-Bag3 Protein-Protein Interaction as a Potential Therapeutic Target in Cancer - Li, Xiaokai (Mol Cancer Ther, 2015)
Heat shock protein 70 (Hsp70) is a stress-inducible molecular chaperone that is required for cancer development at several steps. Targeting the active site of Hsp70 has proven relatively challenging, driving interest in alternative approaches. Hsp70 collaborates with the Bcl2-associated athanogene 3 (Bag3) to promote cell survival through multiple pathways, including FoxM1. Therefore, inhibitors of the Hsp70-Bag3 protein-protein interaction (PPI) may provide a non-canonical way to target this chaperone. We report that JG-98, an allosteric inhibitor of this PPI, indeed has anti-proliferative activity (EC(50) values between 0.3 and 4 μM) across cancer cell lines from multiple origins. JG-98 destabilized FoxM1 and relieved suppression of downstream effectors, including p21 and p27. Based on these findings, JG-98 was evaluated in mice for pharmacokinetics, tolerability and activity in two xenograft models. The results suggested that the Hsp70-Bag3 interaction may be a promising, new target for anti-cancer therapy.